PELAYANAN ADMINISTRASI ONLINE ERA COVID-19 DI KANTOR DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA BINJAI - Andifinika Sari; Mardiansyah Mardiansyah (STKIP PGRI TULUNGAGUNG, 2022)
Anticipating the spread of the covid 19 virus in Binjai City, the Binjai City Population and Civil Registry Service carries out online administrative services in accordance with Circular Number 443.1/2978/Dikcapil as of March 16, 2020. Services are carried out for all areas of work. This policy aims to prevent people from taking care of population administration at the Binjai City Disdukcapil Office. Various benefits of this online service have been felt by the community. This study aims to find out online services in the Covid-19 era at the Binjai City Civil Registry Office. The research methodology of this thesis is descriptive qualitative. Data collection techniques used are Primary and Secondary Data. The results of this study indicate that the online service system is a must in the midst of disrupted public health conditions due to the spread of the covid 19 virus. Although online system services have been implemented since March 2020, there are still various obstacles, including the lack of resources and people's ability to use online devices and no dependence there are still members of the community who do not have android